2019
DOI: 10.1089/jpm.2018.0535
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Hospice Professionals Regarding Medical Cannabis Practices

Abstract: Introduction: With medical cannabis (MC) remaining illegal at the federal level, hospice programs are unsure how to handle requests for MC, particularly since hospice is largely funded with federal dollars. The purpose of this survey was to determine respondents' comfort level with MC use in hospice, what processes and logistics hospice programs are employing when dealing with MC, and to determine what, if any, education hospice programs are providing to their staff. Methods: An anonymous online survey assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 5 publications
3
9
0
Order By: Relevance
“…Some employees received education about medical marijuana, including indications, side-effects, drug interactions, monitoring parameters, legal issues, and proper disposal. 16 The results of the survey of hospice professionals were similar to the results of the survey in part I, reflecting that documentation of medical marijuana is inconsistent, most often listed in the medication profile or medication list. Findings in part III's retrospective chart review also echoed the hospice survey results of indications for symptoms management for medical marijuana use.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Some employees received education about medical marijuana, including indications, side-effects, drug interactions, monitoring parameters, legal issues, and proper disposal. 16 The results of the survey of hospice professionals were similar to the results of the survey in part I, reflecting that documentation of medical marijuana is inconsistent, most often listed in the medication profile or medication list. Findings in part III's retrospective chart review also echoed the hospice survey results of indications for symptoms management for medical marijuana use.…”
Section: Discussionsupporting
confidence: 60%
“…However, one existing publication by Consantino et al shares similar findings and concerns regarding medical marijuana use and documentation among hospice professionals using medical Cannabis. 16 The objectives of the study were to determine employees' comfort level with medical marijuana use in hospice, what processes and logistics hospice programs are employing, and to determine what, if any, education hospice programs are providing to their staff. The survey demonstrated 91% of respondents support medical marijuana use in hospice patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of healthcare professionals in hospices in the United States identified that 40% of staff and volunteers have received no education about medical Cannabis. 82 Currently, there is very little, if any, teaching about Cannabis and cannabinoids on the curriculum for students of medicine, nursing and pharmacy in the United Kingdom. Part of the reason for that apparent deficiency is that curricula on those courses are already full with very high levels of contact time and a requirement for a detailed knowledge base.…”
Section: Barrier 7: Communicating the Knowledgebasementioning
confidence: 99%
“…Moreover, acceptance of MM is widespread among oncology practitioners 2,7,18 . Yet, with limited empiric evidence to support use of MM, health care professionals may not feel sufficiently informed to make specific recommendations 2,7,19,20 . In our study, oncologists seldom initiated discussions about MM.…”
Section: Discussionmentioning
confidence: 85%